CFD Ansys - Fluent Simulation of Prevention of Dioxins Formation Via Controlling Homogeneous Mass and Heat Transfer within Circulated Fluidized Bed Combustor. (August 2015) - Tora, Eman; Dahlquist, Erik
Abstract: Internal mass and heat distribution within a combustor is a key factor of successful combustion process as it influences the contact between the reacting materials and helps reduce formation of undesired products such as dioxins via diminishing emerged hot or cold spots. Nevertheless in case of circulated fluidized bed combustor CFBC, it is difficult to keep a homogeneous heat and mass distribution due to the usage of combusting materials with variable and in some situations unpredictable compositions such as municipal and agricultural wastes. Thus this work investigates CFD Ansys – Fluent simulation as a tool to help the plant operator attain uniform heat and mass transfer via enabling the plant operator to adjust the operating conditions to fit well the used fuel. That is through: (a) visualizing the internal mass and heat distribution within a combustor, (b) manipulating the operating conditions of pressure, velocity, and bed particulates flow rate to determine the correct values considering the inevitable feature of the used fuels, (c) exploring operation deficits and sorting out the problems and (d) studying the feasibility of proposed modifications or changes. An illustrative case study is given as a methodology to demonstrate how likely reasons beyond combustor operation deficits can be defined and tackled. The case study is designed to exemplify the tool to achieve the objective of internal uniform heat and mass transfer within a combustor for given fuel composition and the operating conditions.